Kontruksi ideologi pendidikan Islam pada Sekolah Islam Terpadu dan Kuttab - Aisa Haki Mayasa; Dinda Rahmanida; Eti Ayuningsih; Sutrimo Purnomo (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This research discusses the ideological construction of Islamic education in Integrated Islamic Schools (SIT) and Kuttab in Indonesia after the Reformation. The background of this research starts from the emergence of various Islamic education models that not only play a role as an academic institution, but also as a place to form an Islamic ideology that affects the direction of education. The purpose of this research is to see how the ideology of Islamic education is built in SIT and Kuttab and how both institutions face modernity, state, and national education system. This research uses a qualitative method with the literature study method. This is done through inductive analysis, which includes taking data from relevant primary and secondary sources, then decontextualizing and recontextualizing the data. The data was carefully analyzed to find patterns in the development of Islamic educational ideology today. Research results show that SIT has an ideology that combines religion and science in modern education. Meanwhile, Kuttab has an ideology that aims to revive classical Islamic education based on Al-Qur'an and manners. Both models illustrate the main direction of Islamic education change in Indonesia, namely adaptation to modernity and strengthening tradition. Thus, SIT and Kuttab show differences in ideology that affect the formation of the current Islamic education identity in Indonesia.